Framework for conference management system. - Md Sultan, Abu Bakar; Abdul Ghani, Abdul Azim; Lim, Su Fang (Canadian Center of Science and Education, 2009)
This paper presents a Web-based Conference Management System framework that is intended to support multiple conferences and facilitate the conference management starting from the conference preparation until the attendance tracking process during conference day. The framework derived from the analysis of several web-based related applications. The framework is presents and the results are discussed.